Expression profiling of laccase and peroxidase genes in Schizophyllum commune during differentdevelopment stages - Arya S Raj; KRISHNAPRIYA P J; SONY K B; HEERA G; K P, Sindura (Mushroom Research, 2025)
Schizophyllum commune is a white-rot fungus that can efficiently degrade lignin into low-molecular weight compounds by producing various extracellular lignolytic enzymes, such as laccase and peroxidase. In a previous study, S. commune strain DMRX-2160 was identified as the best S. commune strain in terms of maximum extracellular enzyme activities during both submerged cultivation andsolid-state fermentation. The changes in lignolytic activities across different growth stages, from mycelial run to sporophore formation, was analyzed through gene expression studies of DMRX-2160 cultivated in paddy straw using real-time PCR. Laccase and peroxidase genes were found maximally expressed in the mycelium of DMRX-2160 (42.52 fold for laccase and 4.86 fold for peroxidase than young fruiting body stage). The expression of these genes showed downregulation over the subsequent developmental stages with its lowest expression in young fruiting body stage. The maximum expression of the lignolytic enzyme during the mycelial stage decreased during the fruiting body stage, indicating its increased ability to utilize more nutrients from the substrate degradation.